Mensuração de resultados mercadológicos na perspectiva da avaliação qualitativa: estudo de caso no Sindicato dos Estabelecimentos de Ensino Privado no Estado do Rio Grande do Sul - SINEPE/RS - Ratinecas, Paulo (2010)
The current scenario of organizations shows important changes, in which the marketing analysis of their results is being achieved in a quite different manner from some time ago. Today the assessment of companies needs to overcome their quantitative results. Corporations are looking for tools to measure qualitative variables, they want to know about its credibility, its image and perception of its market positioning. The objective of this study is to identify and analyze the assessment formats that are used by companies to measure the effectiveness of the qualitative results of the organization in relation to the concepts of recognition, reputation, impression, corporate identity, image, quality and satisfaction. The analysis of evidence collected at the company under investigation allowed to identify that the processes of strategic planning and its links to a quality program with its corresponding evaluation process, are the main parameters for measuring the qualitative results. These criteria and analysis, along with control and monitoring of targets and indicators from the strategic planning, are guiding the process of evaluating the results of the company studied